HUBUNGAN SELF-EFFICACY DAN MOTIVASI INTRINSIK DENGAN KEMAMPUAN PEMECAHAN MASALAH SOAL CERITA PERSAMAAN KUADRAT - Pitriani, Pitriani; Hamdani, Hamdani; Yani T, Ahmad; R, Zubaidah; Pasaribu, Revi Lestari (Universitas Tanjungpura, 2025)
This research aims to investigate the correlation between self-efficacy and intrinsic motivation with students' ability to solve quadratic equation story problems among ninth-grade students at SMPN 2 Salatiga. A quantitative approach with a correlational method was employed, involving 29 students from class IX A as participants. Data were collected using problem-solving tests and questionnaires designed to assess self-efficacy and intrinsic motivation. The data were analyzed through Pearson Product Moment correlation and multiple regression techniques. The findings reveal: (1) a moderate and statistically significant positive relationship between self-efficacy and problem-solving performance (r = 0.578); (2) a similarly moderate and significant correlation between intrinsic motivation and problemsolving skills (r = 0.488); and (3) a joint, significant relationship between self-efficacy, intrinsic motivation, and students